Research of the Nonlinear System Identification Based on the Volterra RLS Adaptive Filter Algorithm - Wen Xinling; Chen Yu (Institute of Advanced Engineering and Science, 2013)
This paper mainly research a kind of nonlinear system modeling method based on the Volterra series RLS adaptive filter algorithm. Through the modeling second order Volterra nonlinear system, and adapting Volterra RLS algorithm to apply in the first order and second order item, under the gaussian noise condition, iterations times is not more than fifty times, the algorithm can realize convergence, which prove the algorithm accuracy. Volterra RLS adaptive filter algorithm can be effectively applied into the mechanical vibration damping and de-noising in active control, which has a broad application prospect. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2261